Exploring medical students’ use of principles of self-explanation and structured reflection during clerkship - Chamberland, Martine; Beaudoin, Vanessa; Boulais, Isabelle; Bergeron, Linda; St-Onge, Christina; Dubé, Timothy (Canadian Medical Education Journal, 2023)
Background: While educators observe gaps in clerkship students’ clinical reasoning (CR) skills, students report few opportunities to develop them. This study aims at exploring how students who used self-explanation (SE) and structured reflection (SR) for CR learning during preclinical training, applied these learning strategies during clerkship. Methods: We conducted an explanatory sequential mixed-methods study involving medical students. With a questionnaire, we asked students how frequently they adopted behaviours related to SE and SR during clerkship. Next, we conducted a focus group with students to explore why they adopted these behaviours. Results: Fifty-two of 198 students answered the questionnaire and five participated in a focus group. Specific behaviours adopted varied from 50% to 98%. We identified three themes about why students used these strategies: as “just in time” learning strategies; to deepen their understanding and identify gaps in knowledge; to develop a practical approach to diagnosis. A fourth theme related to the balance between learning and assessment and its consequence on adopting SE behaviours. Conclusions: Students having experienced SE and SR regularly in preclinical training tend to transpose these strategies into the clerkship providing them with a practical way to reflect deliberately and capture learning opportunities of the unpredictable clinical context.